STEMI Coexisted with COVID 19 in a 35-Year-Old Patient - Manouri, Kawtar; Touab, Rida; Snoussi, Nour Elhouda; Oussou, Yousra; Doghmi, Nawal (Cardiology and Cardiovascular Medicine, 2021)
Background: Corona viruses are known to attack the cardiovascular system, and it also appears that the virus may attack the heart muscle directly. Case presentation: We report the case of a 35 year-old-woman admitted for respiratory distress related to COVID 19 infection complicated to myocardial infarction with non-obstructive coronary arteries. Conclusion: The distinction between ischemic and non-ischemic causes of cardiac injury remains difficult given the limitation of additional examinations in this particular context, which maintains confusion in the identification of these breaches.